The Effects of Platelet-Derived Growth Factor-BB on Bone Marrow Stromal Cell-Mediated Vascularized Bone Regeneration - Maolin Zhang; Wenwen Yu; Kunimichi Niibe; Wenjie Zhang; Hiroshi Egusa; Tingting Tang; Xinquan Jiang (Hindawi Limited, 2018)
Regenerative medicine for bone tissue mainly depends on efficient recruitment of endogenous or transplanted stem cells to guide bone regeneration. Platelet-derived growth factor (PDGF) is a functional factor that has been widely used in tissue regeneration and repair. However, the short half-life of PDGF limits its efficacy, and the mechanism by which PDGF regulates stem cell-based bone regeneration still needs to be elucidated. In this study, we established genetically modified PDGF-B-overexpressing bone marrow stromal cells (BMSCs) using a lentiviral vector and then explored the mechanism by which PDGF-BB regulates BMSC-based vascularized bone regeneration. Our results demonstrated that PDGF-BB increased osteogenic differentiation but inhibited adipogenic differentiation of BMSCs via the extracellular signal-related kinase 1/2 (ERK1/2) signaling pathway. In addition, secreted PDGF-BB significantly enhanced human umbilical vein endothelial cell (HUVEC) migration and angiogenesis via the phosphatidylinositol 3 kinase (PI3K)/AKT and ERK1/2 signaling pathways. We evaluated the effect of PDGF-B-modified BMSCs on bone regeneration using a critical-sized rat calvarial defect model. Radiography, micro-CT, and histological analyses revealed that PDGF-BB overexpression improved BMSC-mediated angiogenesis and osteogenesis during bone regeneration. These results suggest that PDGF-BB facilitates BMSC-based bone regeneration by enhancing the osteogenic and angiogenic abilities of BMSCs.